Suitability of Nigeria Portland-limestone cement grades for building's concrete structural members in various exposure classes (2015)
This work investigates the suitability of the Nigerian Portland-limestone cement grades 32.5 and 42.5 for the construction of building structural members in various exposure condition/classes. The investigation was conducted by comparing the 25MPa, 27MPa and 30MPa average cube compressive strengths and the 30MPa, 30Mpa and 31MPa average cube compressive strengths of 1:2:4, 1:1.5:3 and 1:1:2 concretes produced with Portland-limestone cement grades 32.5 and 42.5 respectively with the minimum durability concrete strength requirements for building structural members in Eurocode 2 exposure classes that are obtainable in Nigeria. Investigation revealed that Portland-limestone cement grades 32.5 is only suitable for the construction of superstructure members inside low humidity buildings (class XC1) and is not suitable for the construction of buried building foundations and external building superstructure members. Portland-limestone cement grade 42.5 is only suitable for the construction of superstructure members in exposure classes XC1 and XC2 (building superstructure members subject to long-term water contact) and building foundations buried in non-aggressive natural soils and groundwater. Both cement grades 32.5 and 42.5 are not suitable for the construction of building external superstructure members sheltered from/exposed to rain and subject to high humidity (class XC3) and/or cyclic wet and dry condition (class XC4). Both cement grades are also not suitable for the construction of building foundations buried in aggressive natural soils and groundwater (exposure classes XA1, XA2 and XA3) and building superstructure members in industrial and coastal areas with airborne, waterborne and/or seawater-borne chlorides (exposure classes XD1, XD2, XD3 and XS1).